Hypoxia-Responsive Polymeric Micelles for Enhancing Cancer Treatment - Feng, Huayang; Chu, Dandan; Yang, Fan; Li, Zhanrong; Fan, Bingbing; Jin, Lin; Li, Jingguo (Frontiers in Chemistry, 2020)
Polymer drug vectors have shown great potentials in tumor therapy. However, intelligently controlled release of drug has become a major challenge in nanomedicine research. Hypoxia-responsive polymer micelles have received widespread attention in recent years due to the inherent hypoxic state of tumor tissue. In this study, a novel diblock polymer consisting of polyethylene glycol and poly(glutamic acid (3-(2-nitro-imidazolyl)-propyl)) was synthesized and self-assembled into hypoxia-responsive polymeric micelles for the control-release of chemotherapy drugs. The cell experiments demonstrated that DOX-loaded micelles had a stronger killing capacity on tumor cells under hypoxic conditions, while the blank micelles did not have cytotoxicity. All the experiments indicate that our hypoxia-responsive polymeric micelles have a potential for enhanced cancer treatment.